Challenges and Its Approaches to Bring Integration of Indonesian People - Ulung Napitu; Opan S. Suwartapradja; Budi Radjab; Junardi Harahap (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
This paper deal with the challenges in and approaches to bringing about both and integration in multiethnic Indonesia’s people life. Till now, some challenges in national integration are still found in forms of: SARA (ethnicity, religion, and inter-group)-based social conflicts, fake news (hoax), hate speeches (e.g. Saracen), radical movements, separatism movements, etc. These are due to inequality n social-economic development, low awareness of some elements of the state, and allegedly discriminative practices. Overcoming the multi-dimension problems needs genuine commitment, hard work, allegiance to the Constitusion and Pancasila (Indonesia’s ideological principles) as the state foundation, and awareness of the whole elements of the nation. To analyze deeply the phenomena relating to the callenges in and approaches to bringing about national integration, a library research method was used. Building on written sources of books, journals, newspapers and other prited media, the current paper could expectedly result in a valuable publication. The analysis performed in the present writing started by selecting, evaluating, and analyzing contents and the shynthezing the contents of different books and journals so as to draw conclusions. To secure the validity of the printed sources, the author out both external and internal critiques of the library sources used.